2020
DOI: 10.1002/jbm.b.34719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteogenic and antibacterial properties of strontium/silver‐containing porous TiO2 coatings prepared by micro‐arc oxidation

Abstract: Ti and Ti alloys are bioinert materials and two frequent problems associated with them are bacterial infection and lack of osteogenic potential for rapid bone integration. To overcome the problems, the present study incorporated strontium (Sr) and silver (Ag) simultaneously into porous TiO2 coatings through a single‐step technique, micro‐arc oxidation (MAO). Incorporation of Sr and Ag brought no significant changes to coating micromorphology and physicochemical properties, but endowed TiO2 coatings with both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 36 publications
(146 reference statements)
3
70
0
Order By: Relevance
“…Sengstock et al have found that Ag NPs mitigate the osteogenic differentiation of human MSCs even at nontoxic concentrations, without affecting chondrogenesis [ 38 ]. The incorporation of Ag in TiO 2 coatings exhibited negative effects on early MC3T3-E1 preosteoblast adhesion (within 2 h), mainly due to the toxicity of Ag ions [ 39 ]. However, cell differentiation according to ALP activity was relatively high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sengstock et al have found that Ag NPs mitigate the osteogenic differentiation of human MSCs even at nontoxic concentrations, without affecting chondrogenesis [ 38 ]. The incorporation of Ag in TiO 2 coatings exhibited negative effects on early MC3T3-E1 preosteoblast adhesion (within 2 h), mainly due to the toxicity of Ag ions [ 39 ]. However, cell differentiation according to ALP activity was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Such a dramatic difference in the results can be explained by the significant influence of the silver concentration on the cytological response [ 42 ]. Recently, it has been established that the adherence and viability of the MG-63 and MC3T3-E1 cell differentiation are very sensitive to changes in Ag ion concentration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such results are consistent with those previously reported. 17 , 27 The osteogenic effect of Sr may be due to its release from coatings, which lasted for 30 days, as demonstrated by the release test.…”
Section: Discussionmentioning
confidence: 99%
“…Sr 2+ ion release from the TiO 2 + Sr and TiO 2 + Sr + ICA groups was measured with a method described previously. 17 Briefly, the specimens were immersed in 5 mL phosphate buffer saline (PBS) at pH = 7.4 and incubated at 37°C in a dark environment with gentle stirring for 1, 3, 7, 30 and 120 days. At each time point, the PBS solution was replaced with new PBS and the collected solution was measured with an inductively coupled plasma emission spectrometer (ICP-AES, ICAP 6300, Thermo Fisher Scientific Co) to determine the Sr 2+ level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation